Unwomanly Intellect: Melancholy, Maternity, and Lesbianism in Olive Moore's Spleen. (2nd January 2017) - Wagner, Johanna M.
ABSTRACT: This article examines Ruth, the cerebral protagonist of Olive Moore's novel Spleen, and how her processes of rumination affect the ways she interacts with modern gendered ideologies. These interactions, the article argues, suggest not only a ferocious feminism, but also a kind of homoeroticism or lesbianism extant in the protagonist. In order to make these arguments, the study first analyzes the title of the book, Spleen, mapping out the term's use in medicine and how it is associated with the gendered neurological problem of hysteria approaching the early twentieth century. This association, placed up against melancholy (ennui) from Baudelaire, is then utilized to explore Ruth's ardent intellectual and feminist consciousness by which she refuses modern conventional reproductions of womanhood and maternity. Her refusal leads to the biblical story of Ruth, through which the article then assesses her defiance of heteronormativity via her rejection of heterosexuality and her penchant towards women. Together, these foci create an image of Ruth that suggests not just an extreme feminist character battling a modern melancholy, but further magnify her rejection of the maternal, and her subtler lesbian leanings.